Breeding success and population trends in Adélie penguins in areas with low and high levels of human disturbance - Carlini, A. R.; Coria, Néstor Rubén; Santos, Maria Mercedes; Libertelli, M. M.; Donini, G. (Polar Biology)
The breeding performance and population trends of Adélie penguins (Pygoscelis adeliae) was studied at Esperanza/Hope Bay, Antarctic Peninsula, by comparing an area with low levels of human disturbance (LLD) and an area with high levels of human disturbance (HLD), close to an Argentine research station. From 1995/1996 to 2004/2005 (except for 1999/2000 and 2003/2004), the following population parameters were measured in both areas: (1) the number of breeding pairs, (2) the number of chicks in crèches and (3) the number of chicks produced by breeding pairs.Counts were made for 26 breeding groups situated in the LLD area and 63 breeding groups located in the HLD area. The number of chicks per breeding pair was obtained by following 100 marked nests in each area. All parameters were measured as described in the CCAMLR Monitoring Program protocols. The magnitude and direction (increasing or decreasing) of the changes in breeding population size and the number of chicks crèched were similar in both areas. Overall, the number of breeding pairs decreased from 4,744 to 2,968 (37.4%) in the LLD area, and from 8,744 to 5,378 (38.6%) in the HLD area. The number of chicks fledged increased from 3,808 to 4,065 (6.7%) in the LLD area, and decreased from 6,991 to 6,712 (4%) in the HLD area. Breeding success (chicks fledged per marked nest) did not differ significantly between areas for most of the seasons compared. In 1996/1997, breeding success was significantly higher in the HLD area.Our data suggest that environmental influences currently exert greater effects than human disturbance on the penguin population at Esperanza Bay. Fil: Carlini, A. R. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Coria, Néstor Rubén. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Santos, Maria Mercedes. Ministerio de Relaciones Exteriores, Comercio ...